(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
ABSTRACT Field trials were conducted in 2016 wet season at Institute of Agricultural Research IAR, Research Farm(Lat.11o 11â€™ N, Long. 07038â€™ E, 686m above sea level), Samaru-Zaria and Jaji Military Cantonment Farm located at 30 Km from Zaria along Kaduna â€“ Zaria road (Lat. 10o 49â€™ 25â€ N, Long. 07o 34â€™ 10â€ E, 600m above sea level), both in Northern Guinea Savannah of Nigeria, to Investigate the growth of Maize varieties and dry matter produced at varying timing of nitrogen second dose fertilization. The treatments consist of three maize varieties (SAMMAZ 14, SAMMAZ 15 and SAMMAZ 16) and six times of nitrogen second dose fertilization 4 5, 6, 7, 8, 9 weeks after sowing (WAS). Treatments were factorially combined and laid out in a randomized complete block design (RCBD) with three replications. SAMMAZ 16 outperformed SAMMAZ 14 and SAMMAZ 15 in terms of plant height, number of leaves, total leaf area, leaf area index and dry matter production. Time of nitrogen second dose application 6 WAS consistently produced the highest growth attributes of maize ;plant height, number of leaves, total leaf area, leaf area index and dry matter production compared to other timings evaluated. SAMMAZ 16 and 6 WAS in conclusion appeared to be the optimum for increased maize fodder (dry matter) production in the Savannah region where potential for livestock production is high.